Latex use as an occlusive membrane for guided bone regeneration - Ereno, Cibele; Catanzaro Guimaraes, Sergio A.; Pasetto, Silvana; Herculano, Rondinelli Donizetti [UNESP]; Silva, Cecilia Pereira; Graeff, Carlos Frederico de Oliveira [UNESP]; Tavano, Orivaldo; Baffa, Oswaldo; Kinoshita, Angela (Wiley-liss, 2010)
Latex extracted from Hevea brasiliensis was used as an occlusive membrane for guided bone regeneration. Twenty-four rabbits were divided in two groups: treated and control group. Critical size bone defects (2 cm x 1 cm) were surgically made in the rabbit calvarium. Two latex membranes were implanted in each animal of the treated group, whereas the control defect was filled only with autogenous blood clot. After 15, 30, 60, and 120 days, animals from each group were euthanized, and the samples with regenerated bone were removed. No signs of allergy or rejection were noticed around the calvarial bone defect of the treated group. In the histological analysis, no foreign body inflammatory reaction was observed in the adjacent tissues in contact with the membranes demonstrating that latex can be used at injured sites as an aid in the healing process. Histological analysis, digital radiography, and electron spin resonance were used to evaluate the progress of bone repair. The results show significant differences between groups (p < 0.05) suggesting that latex membranes accelerates healing in critical bone defects. (C) 2010 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 95A: 932-939, 2010.
Keywords: guided bone regeneration; biomaterial; latex; electron spin resonance